Kepuasan Siswa Slta terhadap Penyuluhan Kesehatan Reproduksi Remaja oleh Badan Koordinasi Keluarga Berencana Nasional - Nina Rahmadiliyani; Mubasysyir Hasanbasri; Fitriani Mediastuti (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Adolescent reproductive health program is a description form of the mission of National Family Planning Coordination Body’s Program (BKKBN), which is preparing early qualified human resources in order to create qualified family in 2015. In order to guarantee the rights of sexual and reproductive health youth provision, it is required an integrated and cross-sector effort. Reproductive health education activities that have been conducted in the schools is that health education is integrated into physical education and health lessons and biology.Objectives: This study aims to know the satisfaction of the senior high school students to adolescent reproductive health’s counseling, to know the implementation of adolescent reproductive health counseling and find out the coordination of reproductive health high school adolescents by BKKBN.Method: This research is experimental research with non-analytical with retrospective approach supported quantitative with qualitative methods.Results: Analysis of univariable that students who are not satisfied with adolescent reproductive health’s counseling are important as 30 respondents, the least important of 30 respondents. Bivariable analysis is bivariate relationship between counseling and satisfaction is significantly proven (at 5% error level).Conclusion: Counseling adolescent reproductive health in high school by BKKBN District Klaten not give satisfaction to the students. Implementation counseling adolescent reproductive health by BKKBN District Klaten not meet the needs of students, Espionage activities by BKKBN District Klaten program is still only knowledgeable about the needs of the urgency of adolescent reproduction, School has a new initiative to request assistance from the BKKBN but can not manage the service needs of adolescents. National Family Planning Coordination Body’s Program (BKKBN) is hoping to involve students in implementation strategy program to reach an effective activity.Keywords: satisfaction, implementation, counseling, coordination